1988
DOI: 10.1128/jb.170.11.5200-5207.1988
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of starvation- and glycerol-induced myxospore formation by prior heat shock in Myxococcus xanthus

Abstract: The effect of heat shock on Myxococcus xanthus was investigated during both glycerol-and starvationinduced development. Cells heat shocked at 40°C for 1 h prior to a development-inducing signal displayed an accelerated rate of myxospore formation at 30°C. Additionally, M. xanthus cells heat shocked prior to glycerol induction formed a greater total number of myxospores when sporulation was complete than did control cells maintained at 30°C. However, in starvation-induced fruiting cells the total number of myxo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 24 publications
3
19
0
Order By: Relevance
“…Interestingly, major duplication occurs with the genes encoding molecular chaperones, although some of the duplicated paralogs are not heat induced (Otani et al 2001). As observed in the pulse-chase experiments with 35 S-labeled cells during vegetative growth and spore formation stages, heat-shock genes follow social phase-specific expression patterns (Nelson and Killeen 1986;Killeen and Nelson 1988) and probably support the sociality of these organisms (Weimer et al 1998;Yang et al 1998).…”
Section: Multiple Groels In Myxobacteria-living In Relationmentioning
confidence: 91%
“…Interestingly, major duplication occurs with the genes encoding molecular chaperones, although some of the duplicated paralogs are not heat induced (Otani et al 2001). As observed in the pulse-chase experiments with 35 S-labeled cells during vegetative growth and spore formation stages, heat-shock genes follow social phase-specific expression patterns (Nelson and Killeen 1986;Killeen and Nelson 1988) and probably support the sociality of these organisms (Weimer et al 1998;Yang et al 1998).…”
Section: Multiple Groels In Myxobacteria-living In Relationmentioning
confidence: 91%
“…The pleiotropic phenotypes of dnaK and groEL mutants and biochemical studies have demonstrated that these proteins have physiologically diverse functions due to their role as molecular chaperones; they mediate the correct assembly of other polypeptides (4). However, some organisms may have adapted HSPs for special requirements; HSPs in some prokaryotic and eukaryotic cells have been shown to play a role during development (11,12,20). Significantly, there are reports indicating induction of GroEL at a crucial point of the Streptomyces cell cycle (5).…”
mentioning
confidence: 99%
“…Heat shock prior to chemical induction of development or starvation leads to accelerated and enhanced spore formation. These effects appear to be dependent on the actual expression of heat shock genes, which might sensitize the cells to other stressors to which they subsequently respond more rapidly (15,20).…”
mentioning
confidence: 99%